2015
DOI: 10.1371/journal.pone.0128860
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Evolution of Parasite Resistance in a Warmer Environment: Insights from a Large Scale Field Experiment

Abstract: Global climate change is expected to have major effects on host-parasite dynamics, with potentially enormous consequences for entire ecosystems. To develop an accurate prognostic framework, theoretical models must be supported by empirical research. We investigated potential changes in host-parasite dynamics between a fish parasite, the eyefluke Diplostomum baeri, and an intermediate host, the European perch Perca fluviatilis, in a large-scale semi-enclosed area in the Baltic Sea, the Biotest Lake, which since… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…As an adaptive evolutionary response is determined by the strength of selection and amount of genetic variation, high genetic variation will increase the potential speed with which populations adapt to stressful conditions (Fisher 1930). Our finding may therefore contribute to a greater understanding of the evolutionary responses to global change, which is of critical importance now, when animals are responding to stress caused by unprecedented levels and variability in, for example, temperature (Helmuth et al 2002), humidity (Kellermann et al 2009), starvation (Chippindale et al 1996), competition (Rogell et al 2012), or pathogen levels (Mateos-Gonzalez et al 2015). All these stressors were also included among the experimental treatments used by the studies incorporated in the present meta-analysis.…”
Section: Discussionmentioning
confidence: 96%
“…As an adaptive evolutionary response is determined by the strength of selection and amount of genetic variation, high genetic variation will increase the potential speed with which populations adapt to stressful conditions (Fisher 1930). Our finding may therefore contribute to a greater understanding of the evolutionary responses to global change, which is of critical importance now, when animals are responding to stress caused by unprecedented levels and variability in, for example, temperature (Helmuth et al 2002), humidity (Kellermann et al 2009), starvation (Chippindale et al 1996), competition (Rogell et al 2012), or pathogen levels (Mateos-Gonzalez et al 2015). All these stressors were also included among the experimental treatments used by the studies incorporated in the present meta-analysis.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, a relatively closed habitat may be a key factor for driving the rapid evolution of B. lanceolatum propelled by its weaker ability to buffer against changing ecological factors. Seawater, warmed by a nuclear power plant since 1980 has been reported to cause rapid evolution of parasite resistance in the European perch of the nearly closed Baltic Sea (Mateosgonzalez et al, 2015). Additionally, one of the longer branches in the phylogenetic tree is the branch connecting the amphioxus to the other clades.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has also been shown that the long-term, in situ warming has caused local adaptation as populations of the gastropod grazer Galba truncatula in the heated area have genetically diverged from the nearby populations outside the basin and adapted to the warming in terms of growth rate and survival (Ermold 2016; assessed after 28 years of warming). Moreover, the predatory fish Perca fluviatilis, one of the most common fish species in the heated area, has developed a higher parasite resistance compared to its conspecifics in the nearby archipelago (Mateos-Gonzalez et al 2015; assessed after >30 years of warming). We studied changes in both species assemblage (i.e.…”
Section: Introductionmentioning
confidence: 99%